Cyber-Proletariat: Global Labour in the Digital Vortex - Stevens, Andrew (Labour / Le Travail, 2017)
The article reviews the book, "Cyber-Proletariat: Global Labour in the Digital Vortex," by Nick Dyer-Witheford.